Data Warehousing and Mining. - ITL Education Solutions Limited, ITL Education Solutions Limited (2012)
Data Warehousing and Data Mining is presented in a question-and-answer format following the examination pattern and covers all key topics in the syllabus. The book is designed to make learning fast and effective and is precise, up-to-date and will help students excel in their examinations. The book is part of the Express Learning is a series of books designed as quick reference guides to important undergraduate courses. The organized and accessible format of these books allows students to learn important concepts in an easy-to-understand, question-and-answer format. These portable learning tools have been designed as one-stop references for students to understand and master the subjects by themselves.
Chapter 7: Mining Association Rules -- Generalized Association Rules -- Multi-level Association Rules -- Multidimensional Association Rules -- Multiple Choice Questions -- Answers -- Chapter 8: Classification and Prediction -- Naive Bayesian -- Bayesian Belief Network -- Linear Regression -- Non-linear Regression -- Bagging -- Boosting -- Multiple Choice Questions -- Answers -- Chapter 9: Cluster Analysis -- Statistical Distribution-based Outlier Detection -- Distance-based Outlier Detection -- Density-based Local Outlier Detection -- Deviation-based Outlier Detection -- Multiple Choice Questions -- Answers -- Chapter 10: Advanced Techniques of Data Mining and Its Applications -- Financial Data Analysis -- Retail Industry -- Intrusion Detection -- Telecommunication Industry -- Multiple Choice Questions -- Answers -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books